Animal welfare in biomedical research - Suárez Esquivel, Marcela (2014)
Animal welfare represents a controversial topic that has attracted special interest in recent years, and, consequently, has been brought to the attention of biomedical research. The use of animals has greatly benefited scientific progress in the field of medical research.  However, it has been widely questioned because of its ethical implications. Useful techniques are included in this article to decrease pain and stress in research animals, pursue their welfare, and improve their handling. The paper also includes some definitions and ethical issues to insure animal welfare.  In addition, the national legislation is quoted and discussed. Emphasis is placed on the importance of knowing the species with which the researcher is working, routinely monitoring, and educating those who handle the animals and promoting respect for them.